P152 After-effects of anodal transcranial direct current stimulation on the excitability of the motor cortex in rats. Issue 3 (March 2017) - Koo, H.; Kim, M.S.; Han, S.W.; Kim, Y.- H.; Ko, S.- H.; Shin, Y.- I.
Abstract : Purpose: Transcranial direct current stimulation (tDCS) is increasingly seen as a useful tool for noninvasive cortical neuromodulation. A number of studies in humans have shown that when tDCS is applied to the motor cortex it can modulate cortical excitability. It is especially interesting to note that when applied with sufficient duration and intensity, tDCS can enable long-lasting neuroplastic effects. However, the mechanism by which tDCS exerts its effects on the cortex is not fully understood. We investigated the effects of anodal tDCS under urethane anesthesia on field potentials in in vivo rats. Methods: These were measured on the skull over the right motor cortex of rats immediately after stimulating the left corpus callosum. A Teflon-coated stainless-steel twisted-wire electrode (125 μ m exposed tips; 0.5 mm tip separation) was placed in the left corpus callosum (3.0 mm anterior to bregma, 2.0 mm lateral to midline, 3.0 mm below the dural surface). The electrode position was adjusted in depth to maximize evoked field potentials at the surface of the skull (Fig. 1) . Reference and ground electrodes were attached to the exposed scalp tissue and to a stereotaxic screw. To evoke field potentials in the right motor cortex, biphasic, square-wave constant current stimulation pulses with a duration of 0.1 ms and an intensity of 300 μ A were delivered to the left corpus callosum at 30 s intervals using a A365 stimulus isolator. Anodal tDCS current was applied at an intensity of 250 μ A for 20 min ( n = 8) or 500 μ A for 10 min ( n = 3) using a direct current stimulator. These intensities for tDCS were based on previously reported limits (52, 400 C/m 2 ) for safe stimulation. Results: Evoked field potentials in the motor cortex were gradually increased for more than one hour after anodal tDCS (Fig. 2) . To induce these long-lasting effects, a sufficient duration of stimulation (20 min or more) was found to may be required rather than high stimulation intensity. Conclusion: We propose that anodal tDCS with a sufficient duration of stimulation may modulate transcallosal plasticity. This research was supported by National Research Foundation of Korea (NRF) funded by the Ministry of Education, Science and Technology (NRF-2014R1A2A2A01002501).